CHALLENGES AND ROLE OF MODERN EDUCATION SYSTEMS AND BENEFITS FOR SOCIETY, NATION BUILDING, AND IMPORTANCE - Mansoor Ali, S. Rasheed; N.R, Sangeetha; Sukumar, Biju; Saha, Sohom; Chatterji, Devyani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The modern education system plays a pivotal role in shaping the future of societies and nations. As the world rapidly evolves with technological advancements and globalization, education systems must adapt to meet the changing needs of individuals and communities. This paper explores the challenges faced by contemporary education systems, including issues related to accessibility, quality, and inclusivity. It also examines the crucial role that education plays in nation-building, fostering social cohesion, and driving economic development. Furthermore, the paper highlights the benefits of a well-structured education system, not only for individual empowerment but also for the broader societal and national progress. By addressing the challenges and maximizing the potential of education, societies can ensure sustainable development and a prosperous future for all.